1978
DOI: 10.1071/ar9780411
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Australian Illawarra Shorthorn cattle for resistance to Boophilus microplus. I. Factors affecting resistance

Abstract: Selection and breeding for tick resistance in an Australian Illawarra Shorthorn (AIS) herd was undertaken from 1966 to 1971. Mating of half the AIS herd with a Brahman bull in 1968–69 provided a comparison of tick resistance in selected Bos taurus and crossbred B. taurus x B. indicus cattle. Parent cows and their progeny were ranked for resistance to ticks, infestations of which were acquired as a result of grazing infested pastures, and from periodical artificial infestation with cohorts of c. 20,000 larvae o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
5

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 0 publications
1
24
0
5
Order By: Relevance
“…Contemporary group comparison reveals lighter colored animals are more resistant than dark colored ones (Gasparin et al 2007). Utech et al (1978) and Silva et al (2010) observed that females, pregnant cows and younger animals are more resistant when compare to their respective counterparts.…”
Section: Expression Of Host: Resistance To Ticksmentioning
confidence: 99%
See 2 more Smart Citations
“…Contemporary group comparison reveals lighter colored animals are more resistant than dark colored ones (Gasparin et al 2007). Utech et al (1978) and Silva et al (2010) observed that females, pregnant cows and younger animals are more resistant when compare to their respective counterparts.…”
Section: Expression Of Host: Resistance To Ticksmentioning
confidence: 99%
“…There is uniform agreement that Zebu cattle (Bos indicus) have, on average, greater tick resistance than either European cattle (Bos taurus) or African cattle (Utech et al 1978;Madalena et al 1990;Frisch and O'Neill 1998;Mwangi et al 1998;Wambura et al 1998;da Silva et al 2007). Immunological mediators induced by tick antigens introduced into host skin contribute to the itching sensation which stimulates grooming.…”
Section: Expression Of Host: Resistance To Ticksmentioning
confidence: 99%
See 1 more Smart Citation
“…Tick resistance was assessed by placing a collar containing 20,000 viable tick tarvae on each animat's neck (Utech, Seifert and Wharton, 1978) for 4 h. The number of surviving female ticks, 4 5 mm to 8 mm in tength, present on one side of each animat, 20 days and 2t days after the challenge infestation, was counted independently by two people. The repeatability of tick counts within days was 0 97 for both days and the repeatability between the average count for each day was 0 89.…”
Section: Tick Resistancementioning
confidence: 99%
“…Mesmo em animais da raça Brahman, cerca de 10% dos animais tem apenas moderada resistência aos carrapatos (UTECH et al, 1978). Portanto, ao invés de se usar animais de mediana resistência de raças resistentes, o ideal é utilizar os animais altamente resistentes para aumentar a resistência média de todos os indivíduos da população, de acordo com Martinez et al (2004).…”
Section: Resistência Ao Carrapatounclassified